Effect of Plate Settler Slope in Grease Trap on Oil and Fat Reduction - Andiana, Muhammad Rizky; Karmini, Mimin; Nurjaman, Ujang (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Canteens involve food processing, presentation, and dishwashing activities, which generate domestic wastewater daily from washing used dishes. The canteen wastewater at PT. X contains oil and fat levels exceeding the threshold of 57.4 mg/L, which can harm aquatic ecosystems by inhibiting oxygen transfer into the water and reducing dissolved oxygen concentration (Patel et al., 2021). A grease trap equipped with a plate settler slope can reduce oil and fat levels in wastewater. This experimental study used a pre-test post-test design without control. The population comprised all domestic canteen wastewater at PT. X, with a total of 24 samples (6 pre-test, 18 post-test). Sampling was conducted using grab sampling. Instruments included gravimetric measurement, pH meters, thermometers, and cameras. Data collection involved testing oil and fat levels, measuring wastewater temperature, and pH. Data were analyzed using the Kruskal-Wallis test. Results showed a reduction in oil and fat levels for a 65° plate settler slope of 64.91 mg/L, for a 70° slope of 85.50 mg/L, and for a 75° slope of 92.85 mg/L. A significant difference was found among the three plate settler slopes in reducing oil and fat levels. However, none of the three slopes were effective in achieving oil levels below the standard threshold. Further research is recommended on plate settler slopes greater than 75°.